1996
DOI: 10.1007/bfb0046989
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of cat auditory cortical functional organization after electrical stimulation with a multichannel cochlear implant by means of optical imaging

Abstract: In order to study the effects of acute electrical cochlear stimulation on the topography of the cat auditory cortex, we measured reflectance changes by means of optical imaging of intrinsic signals. Following single pulse electrical stimulation at selected sites of a multichannel implant device, we found topographically restricted response areas. Systematic variation of the stimulation pairs and thus of the cochlear frequency sites revealed a systematic and corresponding shift of the response areas. Increasing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 10 publications
2
17
1
Order By: Relevance
“…In the present study, cochleotopic organization in the ICC was maintained even after very prolonged periods of deafness. This finding is in contrast to previous studies in the auditory cortex (Dinse et al 1997;Hartmann et al 1997;Klinke et al 1999;Schreiner 1999, 2003;Taniguchi et al 1997) suggesting that sustained lack of auditory input and severe degeneration of peripheral innervation result in a degradation of cortical cochleotopic organization. The present results suggest that the cochleotopicity of the ICC is less affected by long-term auditory deprivation than that of the auditory cortex.…”
Section: Cochleotopycontrasting
confidence: 99%
“…In the present study, cochleotopic organization in the ICC was maintained even after very prolonged periods of deafness. This finding is in contrast to previous studies in the auditory cortex (Dinse et al 1997;Hartmann et al 1997;Klinke et al 1999;Schreiner 1999, 2003;Taniguchi et al 1997) suggesting that sustained lack of auditory input and severe degeneration of peripheral innervation result in a degradation of cortical cochleotopic organization. The present results suggest that the cochleotopicity of the ICC is less affected by long-term auditory deprivation than that of the auditory cortex.…”
Section: Cochleotopycontrasting
confidence: 99%
“…In contrast, neonatal deafening results not only in a similar spread of cortical activation as short-term deafness (i.e., a 6 dB supra-threshold stimulus activates a 3-to 4-mm wide dorso-lateral strip), but also in a complete or near-complete loss of the orderly mapping of cochlear location to cortical location (Fallon et al, 2007a;Raggio and Schreiner, 1999). Using optical imaging techniques, Dinse et al (2003Dinse et al ( , 1997a also reported a disintegration of the normal map, with the emergence of isolated islands or patches of activity in response to stimulation of a given electrode. The loss of cochleotopy in AI is in contrast to the electrophysiological evidence from lower centres, most notably the IC, in which a near-normal cochleotopic organisation is maintained even after extended periods of deafness (Leake et al, 2000;Moore et al, 2002;Shepherd et al, 1999;Snyder et al, 1990).…”
Section: Cochleotopic Organisationmentioning
confidence: 93%
“…In early implanted experienced CDCs, however, the auditory cortex displayed activity, indicating that it was functional in these CDCs. Cortical activation with intracochlear electrical stimulation has also been demonstrated using techniques of optical imaging [Dinse et al, 1997]. Scheich [1996, 1997] demonstrated learning effects in gerbil auditory cortex.…”
Section: Cortical Electrical Responsesmentioning
confidence: 99%